2014
DOI: 10.1161/strokeaha.114.005461
|View full text |Cite
|
Sign up to set email alerts
|

Age of Collagen in Intracranial Saccular Aneurysms

Abstract: Background and Purpose The chronological development and natural history of cerebral aneurysms (CA) remains incompletely understood. We used 14C birth dating of a main constituent of CAs, i.e. collagen type I, as an indicator for biosynthesis and turnover of collagen in CAs in relation to human cerebral arteries to further investigate this. Methods Forty-six ruptured and unruptured CA samples from 43 patients as well 10 cadaveric human cerebral arteries were obtained. The age of collagen, extracted and purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…The merit of this model is that it accounts for many different factors that often influence clinical decisions but that were not well studied in previous observational studies, e.g., young age or long life expectancy, coexistent modifiable or nonmodifiable risk factors, coexistent morbidities, morphologic UIA features, or relevance of clinical symptoms related to UIAs. 5,10,11,13,24,25 Admittedly, the UIATS model requires more baseline characteristics, than the PHASES score, which makes its application slightly more time consuming. However, our results highlight that specialists in UIA research and treatment account for these factors in their decisionmaking and that these specialists have a high level of agreement about how to handle these factors for which data are currently incomplete or lacking.…”
Section: Resultsmentioning
confidence: 99%
“…The merit of this model is that it accounts for many different factors that often influence clinical decisions but that were not well studied in previous observational studies, e.g., young age or long life expectancy, coexistent modifiable or nonmodifiable risk factors, coexistent morbidities, morphologic UIA features, or relevance of clinical symptoms related to UIAs. 5,10,11,13,24,25 Admittedly, the UIATS model requires more baseline characteristics, than the PHASES score, which makes its application slightly more time consuming. However, our results highlight that specialists in UIA research and treatment account for these factors in their decisionmaking and that these specialists have a high level of agreement about how to handle these factors for which data are currently incomplete or lacking.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, in many studies, a classification is made of ruptured and unruptured aneurysms according to various criteria: maximum stress, maximum strain, distribution of the direction of collagen fibers, etc. All these results are indicated at different stages of development of aneurysm tissue, which, as shown, continues to develop for even several years [11]. Despite numerous studies in this area, it becomes clear that the main trigger destabilising the body of the aneurysm is still not elucidated.…”
Section: Introductionmentioning
confidence: 86%
“…Hence, synthetic arterial cells must not only increase their production of collagen to increase wall thickness to restore wall stress toward normal in hypertension, they must further increase production to offset the increased loss of collagen. Altered rates of collagen turnover (production and removal) similarly appear to be critical in other cases of arterial disease, including aneurysms [32]. …”
Section: Experimental and Clinical Observationsmentioning
confidence: 99%
“…It was suggested that mechanobiological stability could be the so far unknown biomechanical principle governing the continued enlargement of aneurysms, a hypothesis supported by comparisons with clinical and experimental evidence. Accelerated mass turnover is observed in aneurysms [32, 80] while individuals with stiffer vessels, such as diabetics [81, 82], have a lower risk for rupture. Moreover, in aneurysms (where the stress does in general not equal the homeostatic value) increased mass production or decreased degradation (corresponding to higher kσi in (15)) impairs further dilatation [38, 39].…”
Section: Theoretical Insightsmentioning
confidence: 99%